1984
DOI: 10.1159/000123997
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Oral Melatonin in Humans

Abstract: We administered crystalline melatonin (80 mg) in gelatin capsules to 5 young male volunteers and measured serum and urinary melatonin levels at intervals. Changes in serum melatonin levels were best described by a biexponential equation with an absorption constant (ka) of 1.72 h-1 (half-life = 0.40 h) and an elimination constant (kel) of 0.87 h-1 (half-life = 0.80 h). Peak serum melatonin levels, ranging from 350 to 10,000 times those occurring physiologically at nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
171
2
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(196 citation statements)
references
References 0 publications
19
171
2
4
Order By: Relevance
“…Consistent with numerous previous studies (Deacon and Arendt 1995;Dollins et al 1994;Nickelsen et al 1989;Rutledge et al 2004;Waldhauser et al 1984;Wright et al 1986), melatonin compared to placebo decreased wakefulness. As this effect was not in relation to the memory effects of melatonin, wakefulness can be ruled out as a possible confound.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with numerous previous studies (Deacon and Arendt 1995;Dollins et al 1994;Nickelsen et al 1989;Rutledge et al 2004;Waldhauser et al 1984;Wright et al 1986), melatonin compared to placebo decreased wakefulness. As this effect was not in relation to the memory effects of melatonin, wakefulness can be ruled out as a possible confound.…”
Section: Discussionsupporting
confidence: 90%
“…Second, none of these studies tested memory function during stress, which per se affects memory encoding and retrieval (de Quervain et al 1998;Elzinga et al 2005;Kuhlmann et al 2005b;Leeuwenberg et al 1992). Concurring with the present observations, in adult male rats, melatonin facilitated social recognition (Argyriou et al 1998), and in humans several studies failed to reveal effects of melatonin on memory using free recall procedures (Rutledge et al 2004;Waldhauser et al 1984;Wesensten et al 2005). However, Lieberman et al (1984) found no effect of 240 mg melatonin on both free recall as well as recognition memory of words.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The ingestion of 40-mg capsules is, in fact, known to result in plasma concentrations much above the physiological ones for more than 8 h (Waldhauser et al, 1984;Aldhous et al, 1985), and which have been associated with some biological activities, such as activation of some lymphocyte subsets in cancer patients .…”
Section: Discussionmentioning
confidence: 99%